TOTAL QUALITY MANAGEMENT (TQM) SEBAGAI WUJUD PENINGKATAN MUTU PENDIDIKAN - SARIL Saril (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2019)
Abstract. Total Quality Management (TQM) or Integrated Quality Management (MMT) is a management system that elevates quality as a business strategy and is oriented to customer satisfaction by involving all members of the organization. Integrated Quality Management (MMT) is an approach in running a business that tries to maximize an organization's competitiveness through continuous improvement of its products, services, workforce, processes, and environment. Total Quality Management (TQM) functions effectively in a variety of organizations, namely as a management system to improve product quality or outcomes so that they can be accepted by customers and can avoid the occurrence of fatal errors. Total Quality Management (TQM) aims to provide satisfaction to customer needs as efficiently as possible. According to Margono Slamet, the main objective of TQM is to improve the quality of work, improve productivity and be efficient to satisfy.